Monocyte-to-HDL Cholesterol Ratio Predicts 30-Day Mortality in ST-Elevation Myocardial Infarction Patients Treated with Primary Percutaneous Coronary Intervention - Kurniawan; Yaswir, Rismawati; Deswita Sari; Zelly Dia Rofinda; Dwi Yulia; Syofiati (HM Publisher, 2025)
Background: ST-elevation myocardial infarction (STEMI) is a leading cause of mortality worldwide. Despite advancements in treatment, especially with primary percutaneous coronary intervention (pPCI), 30-day mortality rates remain significant. The monocyte-to-high-density lipoprotein cholesterol ratio (MHR) has emerged as a potential predictor of mortality in STEMI patients, reflecting the balance between inflammation and anti-atherosclerotic processes in atherosclerotic plaques. This study aimed to evaluate the association between MHR and 30-day mortality in STEMI patients undergoing pPCI. Methods: This prospective observational study included 55 STEMI patients treated with pPCI at Dr. M. Djamil General Hospital in Padang, Indonesia, between January and July 2024. Patients were included if they were ≥18 years old, undergoing their first pPCI, and had blood tests done within 24 hours of admission. Patients with prior revascularization, acute/chronic infections, malignancies, autoimmune diseases, or on lipid-lowering therapy were excluded. Blood samples were collected within 24 hours of admission. Monocyte counts were measured using flow cytometry, and HDL cholesterol levels were determined using a homogeneous enzymatic colorimetric method. The MHR was calculated by dividing the monocyte count by the HDL cholesterol level. The primary outcome was 30-day mortality, assessed through hospital records and telephone follow-up. Statistical analysis included chi square, t-tests, and Mann-Whitney U tests. Results: The mean age of the study participants was 59.5 (±11.4) years, with 81.8% being male. The mean monocyte count and MHR were 968 (±212)/mm3 and 28.3 (±6.06), respectively. The median HDL cholesterol level was 33.4 (27-49) mg/dL. Both monocyte count and MHR were significantly higher in patients who died within 30 days compared to those who survived (p<0.001). Conclusion: The MHR is an independent predictor of 30-day mortality in STEMI patients undergoing pPCI. This readily available and cost-effective biomarker may aid in risk stratification and guide treatment strategies for this high-risk population.